Supercritical fluid extraction as a sample preparation technique for the analysis of alpinia galanga - Smith, Roger M. (Roger Malcolm), 1943-; Hasnah Mohd. Sirat; Mohd. Marsin Sanagi; Universiti Teknologi Malaysia. Fakulti Sains. Jabatan Kimia; Simposium Kimia Analisis Kebangsaan (Ke-6 : 1992 : ITM, Shah Alam)
42